2019
DOI: 10.2217/nnm-2018-0337
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different Strategies for Antimicrobial Peptides Incorporation onto/into Lipid Nanocapsules

Abstract: Aim: Over the last decade, antimicrobial peptides (AMPs) have emerged as a promising alternative for the treatment of various infections. The aim of this work is to explore the potential of lipid nanocapsules for the delivery of AMPs. Three approaches were compared in terms of encapsulation efficiency, peptide activity and protection against proteases: peptide encapsulation, surface adsorption or covalent attachment of three selected AMPs. Results: A potentiation of the antimicrobial activity and a partial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Another main strategy to improve the half-life and performance of AMPs is to use advanced delivery vehicles. Interestingly, the use of nanoparticles for the delivery for AMPs has recently been intensely explored, since nanocarriers provide a large surface area for adsorption/encapsulation of AMPs and also enable to prevent peptide self-aggregation [106][107][108][109][110][111][112][113]. In the opinion of the authors, these efforts are most promising with regard to the local delivery of AMPs, whereas meaningful improvements allowing peroral and systemic delivery still remain challenging.…”
Section: Weaknessesmentioning
confidence: 99%
“…Another main strategy to improve the half-life and performance of AMPs is to use advanced delivery vehicles. Interestingly, the use of nanoparticles for the delivery for AMPs has recently been intensely explored, since nanocarriers provide a large surface area for adsorption/encapsulation of AMPs and also enable to prevent peptide self-aggregation [106][107][108][109][110][111][112][113]. In the opinion of the authors, these efforts are most promising with regard to the local delivery of AMPs, whereas meaningful improvements allowing peroral and systemic delivery still remain challenging.…”
Section: Weaknessesmentioning
confidence: 99%
“…Matougui et al explored different approaches for the production of LNCs containing AA230, DPK-060 or LL-37 and found that the adsorption strategy effectively increased their encapsulation, maintained or improved their antimicrobial activity against a set of Grampositive and Gram-negative bacterial strains and enhanced their stability against proteases compared to an AMP solution [71]. Similarly, Groo et al used reverse micelles to encapsulate AP138 in LNCs and showed that the resulting particles maintained antimicrobial activity, while breakdown by proteases was reduced compared to an AP138 solution [72].…”
Section: Lipid Nanocapsulesmentioning
confidence: 99%
“…This short half-life is attributed to protease degradation. The adsorption method may confer a protection against proteolytic degradation, due to PEG on the surface of NEs, which provided steric hindrance and thus blocked interactions between peptide and enzyme [73]. Several studies have been carried out on nanocarriers, i.e., polymeric nanoparticles [40], liposomes [41], functionalized by peptide-22 for glioma treatment.…”
Section: Functionalization Of Tegaserod-loaded Nanoemulsions With Peptide-22mentioning
confidence: 99%
“…In their review of relevant strategies to functionalize lipid-based nanocarriers, Guyon et al mentioned four methods: (i) the direct ligand conjugation on preformed nanocarriers, (ii) the post-insertion of PEG-ligand on preformed nanocarriers, (iii) the incorporation of PEG-ligand during the formulation process and (iv) the noncovalent adsorption of the ligand at the surface of nanocarriers [23]. This last method has already demonstrated its advantages with good adsorption efficiency and preservation of peptide activity [73]. To avoid any possible loss of peptide activity after its covalent link to any PEG moiety, and because of its ease of use and being very fast, we have chosen the peptide adsorption method as valuable option in our formulation assays.…”
Section: Peptide-22 Adsorption On Tg-nesmentioning
confidence: 99%